2019
DOI: 10.3390/ijerph16183377
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Voluntary Policies on Parents’ Ability to Select Healthy Foods in Supermarkets: A Qualitative Study of Australian Parental Views

Abstract: Food packaging is used for marketing purposes, providing consumers with information about product attributes at the point-of-sale and thus influencing food choice. The Australian government focuses on voluntary policies to address inappropriate food marketing, including the Health Star Rating nutrition label. This research explored the way marketing via packaging information influences Australian parents’ ability to select healthy foods for their children, and who parents believe should be responsible for help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Parents intended to create positive structures and routines but were often challenged by time, cost, competing priorities, and other external influences, such as marketing and peer pressure. This is consistent with research that has shown the variety of external factors that can influence parents’ feeding practices [ 16 , 30 , 38 , 47 , 48 ]. Education and support that address family and cultural priorities, and that empower parents by providing strategies and building confidence to overcome external influences while also preventing or addressing internalized feelings of shame or guilt can be beneficial.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Parents intended to create positive structures and routines but were often challenged by time, cost, competing priorities, and other external influences, such as marketing and peer pressure. This is consistent with research that has shown the variety of external factors that can influence parents’ feeding practices [ 16 , 30 , 38 , 47 , 48 ]. Education and support that address family and cultural priorities, and that empower parents by providing strategies and building confidence to overcome external influences while also preventing or addressing internalized feelings of shame or guilt can be beneficial.…”
Section: Discussionsupporting
confidence: 91%
“…For example, just under half of the participants in this study indicated they infrequently introduced new foods to their child. Limited time is a pressure that can result in authoritarian feeding practices that override strategies to develop autonomy [ 18 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of purchases are impulse purchases, and packaging plays a key role in this type of purchase [1][2][3]. Various factors can serve as bases for impulse purchases [4], such as a promotion, personal characteristics, the shop environment, demographic, situational, and social factors [5] and also the perceived health effect of the product.…”
Section: Introductionmentioning
confidence: 99%
“…Food labelling and packaging are used to inform consumers about the product’s characteristics, in accordance with legislation, and for marketing purposes [ 29 ], but they may also provide support for healthier choices [ 30 ]. The legislation regulates the information which may be considered for labelling, and this can sometimes be too bureaucratic and may bring about additional difficulties to market strategies.…”
Section: Literature Surveymentioning
confidence: 99%